Counselling Skills in Everyday Life - Geldard, Kathryn; Geldard, David (Basingstoke : Palgrave Macmillan, 2003)
Most people find themselves listening to other people's problems at some time. The ability to listen properly is clearly an essential attribute in a counsellor. This volume is designed to enhance the counselling skills of non-counsellors as well as help students on counselling courses gain new skills.
Includes index.
Keywords: Counseling; Counseling -- Problems, exercises, etc; Psychology